2011
DOI: 10.1111/j.2040-1124.2011.00189.x
|View full text |Cite
|
Sign up to set email alerts
|

Visceral adipose tissue level, as estimated by the bioimpedance analysis method, is associated with impaired lung function

Abstract: Aims/Introduction:  It has been reported that metabolic syndrome is associated with impaired lung function, and abdominal obesity is regarded as the most important determinant of this association. We evaluated the association between a component of metabolic syndrome, indices of body composition, including the total adipose tissue content, lean bodyweight and visceral adipose tissue content, as assessed by bioimpedance analysis, and lung function.Materials and Methods:  A total of 516 participants responded to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 27 publications
(48 reference statements)
1
8
0
Order By: Relevance
“…Previous studies also found an association of the distribution of FM on PF [ 5 , 6 , 14 , 25 , 29 , 32 39 ]. In the present study, WC was not linearly associated with PF at 18 and 30 years old.…”
Section: Discussionmentioning
confidence: 58%
“…Previous studies also found an association of the distribution of FM on PF [ 5 , 6 , 14 , 25 , 29 , 32 39 ]. In the present study, WC was not linearly associated with PF at 18 and 30 years old.…”
Section: Discussionmentioning
confidence: 58%
“…A total of 570 members from the general population of Fuchu town in Toyama, Japan, participated in a cohort study conducted in 2008, as previously reported (group 1) [27,28] (Fig. 1).…”
Section: Participantsmentioning
confidence: 99%
“…Murine studies have shown that the adiponectin-asthma association is bidirectional, whereby exogenous adiponectin attenuates airway changes in asthma and allergeninduced bronchoprovocation decreases adiponectin concentrations [5,6]. In humans, high levels of adiponectin have reportedly been associated with reduced odds of asthma in pre-menopausal and post-menopausal women in cross-sectional studies [7,8], and low serum previous study (group 1) [27,28], we compared the serum total adiponectin level between asthmatic subjects and non-asthmatic subjects and analyzed the association of the serum total adiponectin level with pulmonary function, including airway reversibility. Second, we enrolled another cohort (group 2) consisting of asthmatic subjects who regularly attended outpatient clinics and non-asthmatic subjects and compared the levels of total, HMW, MMW and LMW adiponectin and the ratio of each adiponectin isoform to the total adiponectin level between the asthmatic and non-asthmatic subjects.…”
mentioning
confidence: 99%
“…Recent reports have indicated that smokers not only have increased abdominal obesity, but also decreased physical activity (PA) and poor nutritional balance [8][9][10][11][12]. In particular, abdominal obesity has been shown to be associated with decreased respiratory function, which is the subject of this study [13]. To the authorsʼ knowledge, however, no comprehensive previous studies have considered these variables.…”
Section: Introductionmentioning
confidence: 82%